Studying the role of thyroid hormone receptor expression in the lacrimal gland in the autoimmune orbitopathy - V. G. Likhvantseva; O. A. Gontyurova; E. A. Rudenko; T. N. Saphonova; K. A. Kuzmin; N. Y. Sviridenko (Oftalʹmologiâ, 2014)
Purpose: To explore the role of thyroid hormone’ receptors in the development of the autoimmune process in orbita.Methods: The intraoperative biopsy material of the lacrimal gland obtained from orbital decompression in patients with autoimmune orbitopathy (AOP) was studied and compared with biopsy material of normal lacrimal gland.Results: The expression of isoforms of thyroid hormone’ receptors in various cellular elements of the lacrimal gland is improved in normal, as well as change their expression when the AOP. This process is associated with change of structure of the lacrimal gland and organ infiltration cells.Conclusion: The findings support the assumption that the lacrimal gland is the target organ, along with orbital and muscles for autoimmune aggression in the AOP.